ANALISIS ARIMA UNTUK MEMPROYEKSI PERTUMBUHAN PENDUDUK DI KOTA METRO - Saputri, Tri Aristi; Febritama, Dani; Moetiara R.A, Allien (Smart Education, 2025)
Abstract: This research intends to project the increase in population of Metro City employing the Autoregressive Integrated Moving Average method. The data utilized encompasses the population figures from 2010 to 2022, sourced from the Office of Population and Civil Registration and the Central Statistics Agency. Data collection was conducted through documentation, and the analysis involved stationarity testing using the Augmented Dickey-Fuller (ADF) test, model identification for ARIMA, projection, and model validation. The analysis results indicate that the ARIMA (2,1,1) model is the most suitable for projecting the population figures. The projection for the year 2023 estimates the total population to reach 154,300 individuals, with separate projections for male and female populations also provided. These projections offer critical insights for government policy planning in addressing the challenges posed by ongoing population growth. This study recommends that future research employ alternative methods and broader data collection to enhance the accuracy of projections.Keyword: ARIMA (Autoregressive Integrated Moving Average), Population Projection, Time Series Analysis, Statistical Modeling. Abstrak: Studi ini diarahkan untuk memproyeksikan peningkatan jumlah penduduk di Kota Metro mengaplikasikan teknik Autoregressive Integrated Moving Average (ARIMA). Data yang dianalisis mencakup jumlah penduduk dari tahun 2010 hingga 2022, yang berasal dari Disdukcapil serta Badan Pusat Statistik. Metode pengumpulan data dilakukan melalui dokumentasi, dan analisis data meliputi uji stasionaritas menggunakan Uji Augmented Dickey-Fuller (ADF), identifikasi model ARIMA, proyeksi, serta validasi model. Hasil analisa menggambarkan model ARIMA (2,1,1) paling sesuai untuk memproyeksikan jumlah penduduk. Proyeksi untuk tahun 2023 menunjukkan total penduduk mencapai 154,300 jiwa, dengan rincian jumlah penduduk laki-laki dan perempuan yang juga diproyeksikan secara terpisah. Hasil proyeksi ini memberikan wawasan penting bagi perencanaan kebijakan pemerintah dalam menghadapi pertumbuhan penduduk yang terus meningkat. Penelitian ini merekomendasikan agar penelitian lanjutan dilaksanakan dengan menerapkan metode yang berbeda dan pengumpulan data yang lebih luas untuk meningkatkan akurasi proyeksi.Kata kunci: ARIMA (Autoregressive Integrated Moving Average), Proyeksi Penduduk, Analisis Deret Waktu, Pemodelan Statistik.